219 β-GLUCAN ENHANCES HEMATOPOIETIC STEM CELL MOBILIZATION. Issue 1 (1st January 2007) - Wagner, S. A.; Cramer, D.; Hansen, R.; Reca, R.; Ratajczak, M.; Li, B.; Laber, D. A.; Yan, J.
Abstract : Background: Peripheral blood stem cell infusion is the preferred method for establishing hematopoiesis in transplantation. G-CSF is now the most commonly used mobilizing agent. Studies have shown that up to 20 to 25% of patients exhibit poor mobilization and are not able to proceed with autotransplantation. β-Glucan is a soluble yeast composed of a β-D-(1-3)-linked glucopyranosyl backbone with γ-D-(1-6)-linked (1-3) side chains. In previous studies, β-glucan has been shown to induce hematopoietic stem and progenitor cell (HSPC) mobilization to the periphery. In this study, we examined β-glucan's ability to mobilize HSPC alone and in conjunction with G-CSF and explored its mechanism of action. Methods: Using the IV form of β-glucan, PGG, dose kinetic, and response studies were done and showed peak stem cell mobilization at 24 hours and maximum results using the 9.2 mg/kg dose. Four groups of wild-type (WT) C57BL/6 mice were used; control, G-CSF only (125 μg/d × 4 days), PGG only (4.8 or 9.2 mg/kg × 1 dose), and G-CSF/PGG combination. In the combination group, G-CSF injections were given daily for 4 days and one PGG injection on day 3. Four hours after the last G-CSF injection, the mice were sacrificed and final white blood cell counts were collected. Blood was assayed for in vitro mobilization in methycellulose culture. Peritoneal macrophage were stimulated with PGG, supernatant was harvested, and concentration of MMP-9 (matrix metalloproteinase-9) was determined using ELISA. Results: All treated groups showed increased mobilization of all major cell lines. β-Glucan alone was able to mobilize peripheral stem cells at both doses. The combination group (G-CSF/PGG-4.8 mg/kg) showed an almost twofold increase in CFU compared with G-CSF alone ( p = .008) β-Glucan mobilizes stem cells via a CR3-independent mechanism and did not induce appreciable levels of cytokine secretion. β-Glucan also stimulated bone marrow-derived macrophages to produce significant amounts of MMP-9. Conclusion: β-Glucan is an agent that enhances stem cell mobilization alone and has a synergistic effect when used in conjunction with G-CSF. The mechanism of mobilization by β-glucan involves MMP-9, which results from release of pro-MMP-9 from marrow macrophages. The efficacy of β-glucan and lack of proinflammatory activity make it an attractive agent to supplement mobilization with G-CSF.